An Audit of Outcomes in Cosmetic Rhinoplasty with the Mandatory Psychiatric Evaluation Protocol - Shandilya, Munish; Bourke, Stephanie; Shandilya, Avi (Facial Plastic Surgery, 2024)
With the high demand of rhinoplasty surgery, careful selection and management of aspirants, as well as proper assessment of outcomes after surgery, are imperative for achieving successful outcomes and learning from it. The aim of this study was to answer two important questions: (1) What is the success rate in cosmetic rhinoplasty? (2) How can we best identify candidates who would achieve good outcomes in cosmetic rhinoplasty? In this study cohort, we excluded patients with any functional concerns and confounding factors that could in any way influence patient satisfaction with a cosmetic surgery. This study is a part of the trilogy of articles on “psychology of rhinoplasty” submitted to this volume of Facial Plastic Surgery, using mandatory psychiatric evaluation (MPE) to optimize candidacy. In total, 184 patients (144 females and 40 males) aged 16 to 63 years (M = 31.09) met the inclusion criteria and were included in this study (follow-up: 3–122 months; M = 70.18 months), and outcome satisfaction was assessed using the visual analog scale (VAS) score and a 5-point Likert scale. The mean improvement between preoperative (M = 4.26) and postoperative VAS scores (M = 8.47) was 4.23. Most patients were happy or very happy (95.1%) about the surgical outcome. Patients who were very happy generally scored between 8 and 10 on the VAS (77.2%) and those who were happy generally scored between 6 and 7.9 (21.2%). Some patients, however, were neutral (3.3%) or unhappy (1.6%) about their surgical outcome, and generally scored around ≤7 on the VAS. Although the successful outcome in 95.1% patients reflects a carefully designed protocol for rhinoplasty candidacy, 4.9% patients reported poor satisfaction despite these efforts. An ever-present proportion of unhappy outcomes is a reality of this popular surgery.
Keywords: rhinoplasty; surgical outcomes; cosmetic surgery; patient satisfaction; psychological assessment